Environmental Crisis or Sustainable Development Opportunity? Transforming the Charcoal Sector in Tanzania : A Policy Note - World Bank (Washington, DC, 2014)
The policy note builds on experience from both Tanzania and other Sub-Saharan African countries with similar socioeconomic and environmental contexts. This policy note puts forward and discusses a range of policy measures along the entire charcoal value chain in Tanzania. The development of this policy note benefited from a variety of recent studies on charcoal utilization and trade conducted in the country. This policy note is structured as follows: chapter two provides a broad overview of the charcoal sector in Tanzania and some of the key challenges being faced. It also includes a summary of the key legal and policy measures that have been taken over the past two decades and an assessment of how successful they have been in effecting positive change. Following this, chapter three summarizes experiences reforming the charcoal sector in Tanzania and elsewhere, as well as an assessment of how successful these measures have been. Where possible, key lessons learned are extracted and used to inform policy recommendations. In chapter four, key policy recommendations are made along the production and marketing chains, which are hoped, will provide a useful resource for policy makers and implementers. Chapter five assesses the likely impact of the reforms on reducing deforestation and forest degradation, as well as the positive impacts on boosting employment and improving rural livelihoods. The chapter concludes with an assessment of the costs of the policy recommendations made.